Risk factors for the incident of respiratory distress syndrome in neonates at the Regional General Hospital of Buleleng District, 2020 - Suarmini, Kadek Ayu; Megaputri, Putu Sukma; Susiana, Ni Komang; Purnami, Luh Ayu (Alma Ata University Press, 2024)
Background : The main causes of death in neonates are complications of pregnancy and childbirth, such as asphyxia, sepsis and low birth weight complications. Respiratory Distress Syndrome (RDS) is a condition related to the respiratory system of neonates. The large number of RDS cases is one of the highest causes of death in neonates.Objectives: The aim of this study is to determine the risk factors for the incidence of RDS at Buleleng District Hospital, especially in premature neonates in 2020.Methods: This research method uses a retrospective cohort study. Where the data was taken using secondary data in the NICCU room at Buleleng Regional Hospital. The independent variables included are the characteristics of the neonate including gestational age, history of hypertension experienced by the mother during pregnancy, birth weight, history of premature rupture of membranes, history of asphyxia experienced during the birth process. The dependent variable in this study was the incidence of RDS in neonates. The sample included in this research was 64 mothers who gave birth at the Buleleng District Hospital in 2020. This research used univariate analysis to assess the frequency distribution of each variable, then continued using bivariate analysis to determine the variables that were included in the multivariate analysis. Multivariate analysis was carried out computerized using logistic regressionResults: The results of this study found that there were 2 risk factors that directly increased the incidence of RDS in neonates including premature gestational age with a value of p 0.01 (19.8, 95% CI 1.8-133.7, low birth weight ( 2.9, 95% CI 1.9-8.4). Conclusions: The conclusion is that there are 2 risk factors that are associated and increase the incidence of RDS in neonates, namely premature gestational age and low birth weight.